DSC119: Data Visualization and Information Reporting / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2020)
This course intends to introduce concepts and practices behind effective data visualization and reporting. The course explores current data visualization that is analyzed for the content, methods and design strategies. The objective is to provide students with analytical tools that can benefit the design process of visualizing data and reporting knowledge behind the data.